La responsabilidad penal de los adolescentes en conflicto con la ley penal, por la realización de delitos que no admiten amnistía o indulto dentro de la jurisdicción especial para la paz - Ortega Galindo, Doris (Archivos de criminología, seguridad privada y criminalística, 2022)
This article covers a constitutional perspective and international criminal responsibility for adolescents, their applicability and possible corrections to this is to make for precise efficiency in order to mark a parameter the effectiveness and efficiency d law equally not reform as such but social different alternatives proposed for the application of the law is effective and that such offenders out of the system not by a social rehabilitation or re-education not to carry anything but a mechanism of penetration gaps these subjects leads to crime, thus not stigmatize but the root of the flaw and state showed alternative psychological, moral and ethical for correction, determining them as persons of special constitutional protection was found.